Suicidal Behavior in Emergency Child and Adolescent Psychiatric Service Users Before and During the 16 Months of the COVID-19 Pandemic - Kirič, Barbara; Leben Novak, Lara; Lušicky, Petra; Drobnič Radobuljac, Maja (Frontiers in Psychiatry, 2022)
Background: Slovenia is among the countries with the highest suicide rates in the world. The COVID-19 pandemic has had a significant impact on the mental health of children and adolescents. Our hypothesis is that the school closure during the pandemic with a gradual transfer to virtual schooling had an important impact on children’s and adolescents’ suicidal behavior. Therefore, we aimed to determine possible changes in the frequency assessments as well as frequency and severity of suicidal behavior in the population of Slovene children and adolescents seeking emergency psychiatric help in correlation with the progression of the pandemic and online schooling. Methods: We performed a retrospective observational analysis of medical records of all children and adolescents referred to the only 24-hour emergency in- and outpatient child and adolescent psychiatry service in Slovenia from March 2019 through the end of July 2021. We extracted number of assessments, number of patients with suicidal ideation and with attempted suicide. A comparison between the same periods prior to the pandemic and during the pandemic was made. The months of school closure due to the COVID-19 restriction measures and the months without closures were also compared. Results: During this period, 1966 children and adolescents were assessed. There was no statistically significant difference in the observed frequency of emergency visits when we compared all the months with to all the months without school closures, or when individual corresponding months with and without school closures were compared. However, there were statistically significantly more patients with suicidal ideation (t(16)=-2.739, p=0.015; W=25.0, p=0.016) and patients who had attempted suicide (t(16)=-3.412, p=0.004; W=14.5, p=0.006) during the pandemic as individually compared to the corresponding pre-pandemic months. Conclusions: Our results show that the number of Slovene children and adolescents who required emergency psychiatric help with suicidality and attempted suicide increased during the COVID-19 pandemic. The increase was shown only after the first year of the pandemic. The observed increase did not appear to directly correspond to the school closures, but was more likely related to the duration of the pandemic.